Analisis Pengendalian Kualitas Produksi dengan Menggunakan Pendekatan Logika Fuzzy Failure Mode and Effect Analysis (FMEA) - Muzani, M. Aldi; Luthfianto, Saufik (UNIB Press, 2025)
The rapid growth of the manufacturing industry demands that companies continuously enhance product quality to meet consumer needs and maintain competitiveness in the global market. In this context, quality control becomes a strategic element that not only ensures product consistency but also influences corporate reputation and operational efficiency. This study was conducted at PT Industri Komkar Indonesia, a manufacturing company specializing in rubber components, particularly rubber bust boots. The research aims to identify the factors contributing to product defects and uncover the root causes that may reduce customer satisfaction. The method employed is Fuzzy Failure Mode and Effects Analysis (Fuzzy FMEA), an approach capable of addressing uncertainty in risk assessment through the application of fuzzy logic. Calculations are carried out by evaluating the Fuzzy Risk Priority Number (FRPN) for each potential failure mode. The analysis reveals that machine breakdowns or suboptimal machine conditions are the primary causes of product defects. Therefore, corrective actions are essential, including routine machine maintenance, enhanced operator training, and stricter monitoring of the production process. These measures are expected to reduce product failure rates, improve customer satisfaction, and lower production costs resulting from defective products.